2018
DOI: 10.14814/phy2.13790
|View full text |Cite
|
Sign up to set email alerts
|

Intestine-specific expression of human chimeric intestinal alkaline phosphatase attenuates Western diet-induced barrier dysfunction and glucose intolerance

Abstract: Intestinal epithelial cell derived alkaline phosphatase (IAP) dephosphorylates/detoxifies bacterial endotoxin lipopolysaccharide (LPS) in the gut lumen. We have earlier demonstrated that consumption of high‐fat high‐cholesterol containing western type‐diet (WD) significantly reduces IAP activity, increases intestinal permeability leading to increased plasma levels of LPS and glucose intolerance. Furthermore, oral supplementation with curcumin that increased IAP activity improved intestinal barrier function as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 43 publications
2
36
0
Order By: Relevance
“…In addition, in experimental liver disease induced by bile duct ligation or CCl 4 exposure, oral IAP administration attenuated the compromised intestinal barrier permeability and liver fibrosis, in association with reduced LPS absorption [ 42 ]. Furthermore, intestine-specific overexpression of a chimeric alkaline phosphatase attenuated the metabolic syndrome induced by a western diet [ 43 ]. A second important function proposed for IAP is dephosphorylation of CD36 and modulation of fatty acid (FA) uptake [ 44 , 45 ].…”
Section: Tnap’s Pathophysiological Functions In the Liver Bile And Intestinal Lumenmentioning
confidence: 99%
“…In addition, in experimental liver disease induced by bile duct ligation or CCl 4 exposure, oral IAP administration attenuated the compromised intestinal barrier permeability and liver fibrosis, in association with reduced LPS absorption [ 42 ]. Furthermore, intestine-specific overexpression of a chimeric alkaline phosphatase attenuated the metabolic syndrome induced by a western diet [ 43 ]. A second important function proposed for IAP is dephosphorylation of CD36 and modulation of fatty acid (FA) uptake [ 44 , 45 ].…”
Section: Tnap’s Pathophysiological Functions In the Liver Bile And Intestinal Lumenmentioning
confidence: 99%
“…Exogenous IAP administration was suggested to improve the IB function, while oral or enteral administration of IAP ameliorated the disintegrated IB [116,117]. It was recently reported that high fat, Western-type diet-induced IB dysfunction, improved glucose intolerance, and orally administered IAP improved severe ulcerative colitis patients [118]. Since it was reported that anti-TNFα antibodies and inhibition of myosin light chain kinase (MLCK) prevented the impaired barrier function, treatment with these antibodies and inhibitors was suggested to reduce the severity of inflammatory bowel diseases.…”
Section: Modulation Of Immune Function and Oxidative Stressmentioning
confidence: 99%
“…By far, the most convenient route of administration of medicines is oral, for subsequent enteral absorption. Following oral administration, ingested curcumin passes through the stomach, where practically no absorption takes place [ 7 ], and it is then detected in the intestine [ 8 , 9 ]. However, curcumin is then metabolized extensively during first-pass metabolism [ 10 ], which results in low bioavailability.…”
Section: Introduction: the Need To Protect Curcumin In The Bodymentioning
confidence: 99%